2006
DOI: 10.1103/physreve.73.036614
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal description of X waves in quadratic nonlinear materials

Abstract: We study localized light bullets and X waves in quadratic media and show how the notion of nonlocality can provide an alternative simple physical picture of both types of multidimensional nonlinear waves. For X waves we show that a local cascading limit in terms of a nonlinear Schrödinger equation does not exist-one needs to use the nonlocal description, because the nonlocal response function does not converge toward a ␦ function.Also, we use the nonlocal theory to show that the coupling to the second harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…A similar type of behavior occurs in the multidimensional analogue of (1) and (2), which recently has been used to model light bullets and X -waves in quadratic media [22]. When neglecting the slowly varying term i∂ z e 2 by assuming (7), one ends up with a multidimensional analogue to (8)- (12).…”
Section: Introductionmentioning
confidence: 92%
“…A similar type of behavior occurs in the multidimensional analogue of (1) and (2), which recently has been used to model light bullets and X -waves in quadratic media [22]. When neglecting the slowly varying term i∂ z e 2 by assuming (7), one ends up with a multidimensional analogue to (8)- (12).…”
Section: Introductionmentioning
confidence: 92%
“…In what follows we will use the normalization (6) 013826-1 ©2010 The American Physical Society nonlocal response is determined by the details of the physical process responsible for the nonlocality. For all diffusion-type nonlinearities [26], orientational-type nonlinearities (like nematic liquid crystal) [23], and for the general quadratic nonlinearity describing parametric interaction [27][28][29][30], the response function is an exponential R(x) = (2σ ) −1 exp(−|x|/σ ) originating from a Lorentzian in the Fourier domain, with σ > 0 defining the degree of nonlocality. Interestingly, for parametric interaction, the response function can also be periodic, R(x) ∝ sin(|x|/σ ) in certain regimes of the parameter space [31].…”
Section: The Nonlocal Model and The Response Functionmentioning
confidence: 99%
“…Until now, the stationary regime was argued to be when the characteristic GVM length is 4 times longer than the SHG coherence length [1], while a more accurate perturbative description showed that the FW has a GVM-induced Raman-like term [4,5], which must be small for the system to be in the stationary regime [4]. However, no precise definition of the transition between the regimes exists.On the other hand, the concept of nonlocality provides accurate predictions of quadratic spatial solitons [6,7], and many other physical systems (see [8] for a review). Here we introduce the concept of nonlocality to the temporal regime and soliton pulse compression in quadratic nonlinear materials.…”
mentioning
confidence: 99%
“…On the other hand, the concept of nonlocality provides accurate predictions of quadratic spatial solitons [6,7], and many other physical systems (see [8] for a review). Here we introduce the concept of nonlocality to the temporal regime and soliton pulse compression in quadratic nonlinear materials.…”
mentioning
confidence: 99%